Development of a low‐cost food color monitoring system. Issue 2 (7th October 2020) - Jain, Ankit; Pradhan, Bikash K.; Mahapatra, Paresh; Ray, Sirsendu S.; Chakravarty, Sumit; Pal, Kunal
Abstract: The colorimetric analysis of food has gained much popularity in the last few decades. The present study reports the development of a low‐cost food color quality testing and process monitoring system. The proposed device consists of a hardware and a software (Color Magic) combination, which may allow the hardware to be used either for quality testing or process monitoring applications. In the quality‐testing mode, the software captures the image of the food products through the imaging system. Subsequently, the software processes the acquired image and computes color parameters in RGB (red, green, blue), CIELAB, and HSI (hue, saturation, intensity) color spaces. The software also synthesizes and displays the perceived color information in the display panel. The datalog of the sample color information can be sent to the user. Further, a separate software (Color Process), which is installed in a central server, was developed to implement a wireless star network topology for multi‐node process monitoring. The "Color Process" software allows users to acquire color information from multiple hardware. The software monitors the Hue from all the devices. It alerts the user via email if the Hue is beyond the range in any of the nodes. Finally, the device was tested for quality testing and process monitoring applications using colored placards and apple slices. The implementation of the wireless sensor network (WSN) in designing the multi‐node process monitoring makes the proposed device a unique system. This further would allow the device to be used for process monitoring at multiple remote locations.